Eating disorders in individuals with Attention Deficit Hyperactivity Disorder (Research, Society and Development, 2024)
There is no doubt that the number of people suffering from diseases related to human behavior has increased in recent years. Seeking guidance from experts in the field is necessary to avoid complications and lack of adequate treatment. Eating disorders are classified as multifactorial mental disorders and are characterized by unhealthy eating habits and negative attitudes towards food. The study addressed the link between eating disorders (EDs) and Attention Deficit Hyperactivity Disorder (ADHD) through a literature review to understand the chosen topic with a qualitative and objective approach, analyzing references, scientific articles, magazines and published books at an average interval over the last 10 years. The characteristics of anorexia nervosa, bulimia nervosa and binge eating disorder were highlighted, where it was found that anorexia nervosa has a higher mortality rate, while bulimia nervosa has a lower rate, but brings greater functional impairment. Given the analyses, the main results found point to a relationship between eating disorders and attention deficit, showing that additives, sugar, preservatives can worsen symptoms. Furthermore, it addresses the importance of a balanced diet, rich in nutrients and vitamins as a complementary way to conventional treatment, reducing symptoms and improving the quality of life of these individuals. Our objective is to provide scientific information about the importance of nutrition to improve the quality of life of those suffering from eating disorders (ED) and attention deficit hyperactivity disorder (ADHD).